2010
DOI: 10.1002/jat.1541
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of acute toxicity of 188Re–BMEDA–liposome in rats

Abstract: Liposomes can selectively target cancer sites and carry payloads, thereby improving diagnostic and therapeutic effectiveness and reducing toxicity. To evaluate therapeutic strategies, it is essential to use animal models reflecting important safety aspects before clinical application. The objective of this study was to investigate acute radiotoxicity of ¹⁸⁸Re-N,N-bis (2-mercaptoethyl)-N',N'-diethylethylenediamine (BMEDA)-labeled pegylated liposomes (¹⁸⁸Re-BMEDA-liposome) in Sprague-Dawley rats. Rats were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(28 reference statements)
0
10
0
Order By: Relevance
“…The toxicity observed was similar to that reported for 188 Re-BMEDA-liposomes. 28 Kidneys are radiosensitive…”
Section: -234748mentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity observed was similar to that reported for 188 Re-BMEDA-liposomes. 28 Kidneys are radiosensitive…”
Section: -234748mentioning
confidence: 99%
“…26,27 A significant theoretical advantage was the low dose delivered to the bone marrow for radiolabeled liposomes compared with radiolabeled antibodies. 26,27 Preclinical studies of 188 Re-liposomes have also shown the acute toxicity 28 and potential of this therapy in colon carcinoma. [29][30][31][32] A simple method of encapsulating rhenium radionuclides into liposomes and Doxil using N,N-bis(2-mercaptoethyl)-N¢,N¢-diethylethylenediamine (BMEDA) with high labeling efficiency and good stability has been reported.…”
mentioning
confidence: 99%
“…Our previous findings suggest that 188 Rhenium‐labeled pegylated liposomes ( 188 Re‐liposome) is a promising candidate for cancer therapy in C26 murine colon carcinoma ascites (Chang et al ., ; Chen et al ., , ) and a solid tumor model (Chang et al ., , , ). In addition, a 14‐day acute toxicity study was also performed to evaluate radiotoxicity of 188 Re‐liposome in rodents (Liu et al ., ). Although none of the rats died and no clinical sign was observed during the study period, rats administered with 185 MBq of 188 Re‐liposome displayed a significant decrease in white blood cell (WBC) counts 7 days postinjection.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the 188 Re-labeled liposome encapsulated with doxorubicin as a bimodal radiochemotherapeutic agent has been recently investigated in a series of translational studies for cancer treatment using animal models with colon cancer and related ascites. [16][17][18][19][20][21]25 In this current study, the 188 Re-BMEDA complexencapsulated neutral PEGylated liposomes (abbreviated as 188 Re-Liposome) was prepared and evaluated as a diagnostic and therapeutic agent for glioma. An orthotopic glioma tumor-bearing rat model (Fischer/F98) was prepared to mimic the behavior of human malignant astrocytomas for the study.…”
Section: Introductionmentioning
confidence: 99%